(untitled) (Construction Economics and Building, 2014)
The aim of this paper is to propose a new framework for structuring contract types and payment methods. Concerning procurement contracts, the first important new feature of this framework is a stepwise structure with three main steps in the contract design: (1) what will be procured—should the contract only include construction, or should it include both construction and operation/maintenance (2) who will do the detailed design of the premise and (3) how many contractors will the client use? The second important new feature of this framework is that both step 2 and step 3 include a continuum of alternatives. Concerning payment methods, the new framework is primarily based on how the specific risks of the project are shared. These frameworks can be useful for policy formulation in that they can help to avoid some problematic ways of formulating policies.